ЗАСТОСУВАННЯ МЕТОДУ МАКРОМОДЕЛЮВАННЯ ЯК ОСНОВИ ДЛЯ ПРОГНОЗУВАННЯ ЕЛЕКТРОСПОЖИВАННЯ БАГАТОКВАРТИРНИХ БУДИНКІВ - Лежнюк, П.Д.; Бондарчук, А.С.; Гоголюк, О.П. (Інститут електродинаміки НАН України, Київ, 2019)
The application of the method of macromodelling is proposed for single-factor modeling and analysis of daily schedules of household electricity consumers, which creates the basis for their prediction at various time intervals. The advantage of the method is that it allows, with an accuracy sufficient for practical application, to create deterministic models of power consumption based on the initial information without the need for its preliminary processing.  References 10, figures 5.